2020
DOI: 10.1109/access.2020.2976537
|View full text |Cite
|
Sign up to set email alerts
|

Data Rate Enhancement in Optical Camera Communications Using an Artificial Neural Network Equaliser

Abstract: In optical camera communication (OCC) systems leverage on the use of commercial off-the-shelf image sensors to perceive the spatial and temporal variation of light intensity to enable data transmission. However, the transmission data rate is mainly limited by the exposure time and the frame rate of the camera. In addition, the camera's sampling will introduce intersymbol interference (ISI), which will degrade the system performance. In this paper, an artificial neural network (ANN)-based equaliser with the ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…At each user, an N number of photodetector (PD) receivers is located to receive and recover transmitted data streams. The use of non-imaging MIMO VLC system offer a wide field-of-view and a high optical gain compared with imaging MIMO receivers [14], [15].…”
Section: Mimo Vlc Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…At each user, an N number of photodetector (PD) receivers is located to receive and recover transmitted data streams. The use of non-imaging MIMO VLC system offer a wide field-of-view and a high optical gain compared with imaging MIMO receivers [14], [15].…”
Section: Mimo Vlc Modellingmentioning
confidence: 99%
“…The diversity in communications systems (i.e., VLC with MIMO in this case), which is adopted to improve the system performance (i.e., transmission capacity, link availability, etc. ), depends on several factors including the field of view [2], type of receivers, i.e., non-imaging or imaging [14], the type of diversity schemes such as angle diversity [15] and maximal ratio combining (MRC). By knowing the full CSI from sending a pilot signal (PS), or in this case the channel matrix H, the VLC receiver is able to fully recover the transmitted data where the received signal m rec is given by:…”
Section: Mimo Vlc Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…In IS-based VLP, image-processing techniques can be used to determine the position but at the cost of increased complexity [ 12 ]. Note that, in VLP the transmission speeds (i.e., data rates) of the PD and IS are not critical at all since the aim is to achieve positioning with high accuracy [ 13 ]. Most research reported on VLP has focused on the investigation of geometrical properties using triangulation/trilateration, fingerprinting, or proximity methods to determine the transmission distance based on establishing a one-to-one relationship between the target location and its received signal strength (RSS).…”
Section: Introductionmentioning
confidence: 99%
“…However, the low data rate R b feature of optical camera communications (OCC) should not be seen as a problem, considering that there are many applications, including VC [ 16 ], indoor localization [ 16 ], Internet of Things (IoT) [ 16 ], sensor networks, motion capturing [ 17 ], and advertising [ 18 ], where R b is considerably low. In OCC systems, each pixel at the receiving image sensor can detect signals at different wavelengths over the visible range, e.g., red, green, and blue (RGB), hence offering parallel detection capabilities, an adaptive field of view feature, and even enhanced R b using multiple-input multiple-output [ 16 , 19 ] and artificial neural network-based equalizers [ 20 ]. In addition, the information carrying light beams from different sources and many directions via the line-of-sight (LOS) [ 21 , 22 ], non-LOS, and/or both paths [ 23 ] can be captured using the camera-based Rxs with the extended transmission range [ 24 ] compared with the PD-based links.…”
Section: Introductionmentioning
confidence: 99%